Post-Consumer Recycled Pet Packaging for Fresh Berries: A Comparative Study Between Incorporating an Antifungal Agent Superficially and into the Main Body of the Packaging - Junqueira-Conceicao Goncalve, M (Springer New York LLC, 2014)
This study proposes to incorporate an antifungal agent (potassium sorbate, KS) to post-consumer recycled polyethylene terephthalate (PCRPET), by adding KS to the dip solution through which PCRPET normally passes after extrusion, in order to acquire a non-stick silicone coating, which prevents individual packages from adhering to each other while stacked. This method of imparting antifungal activity to the packaging is far more advantageous than adding KS to the extruder feed because it results in virtually no alterations to the colour and mechanical properties of PCRPET, which is a major issue when KS is added to the extruder feed. The antifungal efficacy of the active packaging was demonstrated against Botrytis cinerea growth by a novel method which mimics the action of the antifungal agent under fruit contact conditions. A reduction by 2 log cycles was observed when the initial concentration of the mould was 105 conidia/mL. The active packaging was effective over a test period lasting 6 months. The packaging microstructure was visualized by scanning electron microscopy (SEM); its thermal properties were characterized using a differential scanning calorimeter (DSC); its optical properties were characterized using CIE Lab colorimetry; and its mechanical properties were characterized by measuring resistance to dynamic compression. The mechanical properties showed no significant difference (P > 0.05) with those of the control (PCRPET without KS), and despite a statistically significant difference (P < 0.05) in the colour parameters (L*, a* and b*), the total colour difference (?E*) was found to be too small to be visually noticed. This study achieved the aim of adding antifungal activity to PCRPET packaging with little or no perceptible changes to its mechanical, thermal and optical properties and virtually no changes being made to the standard high-speed packaging production line. © 2014 Springer Science+Business Media New York.